Midodrine as adjunctive support for treatment of refractory hypotension in the intensive care unit: A multicenter, randomized, placebo controlled trial (the MIDAS trial) - Anstey, Matthew; Wibrow, B.; Thevathasan, T.; Roberts, B.; Chhangani, K.; Ng, P.; Levine, A.; DiBiasio, A.; Sarge, T.; Eikermann, M. (2017)
© 2017 The Author(s).Background: Patients admitted to intensive care units (ICU) are often treated with intravenous (IV) vasopressors. Persistent hypotension and dependence on IV vasopressors in otherwise resuscitated patients lead to delay in discharge from ICU. Midodrine is an oral alpha-1 adrenergic agonist approved for treatment of symptomatic orthostatic hypotension. This trial aims to evaluate whether oral administration of midodrine is an effective adjunct to standard therapy to reduce the duration of IV vasopressor treatment, and allow earlier discharge from ICU and hospital. Methods: The MIDAS trial is an international, multicenter, randomized, double-blind, placebo-controlled clinical trial being conducted in the USA and Australia. We are targeting 120 patients. Adult patients admitted to the ICU who are resuscitated and otherwise stable on low dose IV vasopressors for at least 24 h will be considered for recruitment. Participants will be randomized to receive midodrine (20 mg) or placebo three times a day, in addition to standard care. The primary outcome is time (hours) from initiation of midodrine or placebo to discontinuation of IV vasopressors. Secondary outcomes include time (hours) from ICU admission to discharge readiness, ICU length of stay (LOS) (days), hospital LOS (days), rates of ICU readmission, and rates of adverse events related to midodrine administration. Discussion: Midodrine is approved by the Food and Drug Administration (FDA) for the treatment of symptomatic orthostatic hypotension. In August 2010, FDA proposed to withdraw approval of midodrine because of lack of studies that verify the clinical benefit of the drug. We obtained Investigational New Drug (IND 113,330) approval to study its effects in critically ill patients who require IV vasopressors but are otherwise ready for discharge from the ICU. A pilot observational study in a cohort of surgical ICU patients showed that the rate of decline in vasopressor requirements increased after initiation of midodrine treatment. We hypothesize that midodrine administration is effective to wean IV vasopressors and shorten ICU and hospital LOS. This trial may have significant implications on lowering costs of hospital care and obtaining FDA approval for new indications for midodrine. Trial Registration: This study has been registered at clinicaltrials.gov on 02/09/2012 (NCT01531959).